Parent-child relationship, perceived social support, perceived discrimination as predictors of well-being among LGBTQ emerging adults in Malaysia - Haw, Ying Huei; Lee, Nie; Yashnevathy, Govindasamy (2023)
Malaysian LGBTQ emerging adults’ well-being is essential to examine as better well-being can help them to cope with the struggles due to their sexual minority identity. This paper aimed to investigate the role of positive and negative parent-child relationships, perceived social support, and perceived discrimination as predictors of well-being among LGBTQ emerging adults in Malaysia. A cross-sectional quantitative study using purposive and snowball sampling techniques was conducted. 148 LGBTQ emerging adults aged between 18 and 29 (M = 22.4, SD = 2.9) were recruited via the online platform. The linear regression model shows a significant predicting effect of the positive and negative parent-child relationship, perceived social support, and perceived discrimination on well-being among Malaysian LGBTQ emerging adults. The results indicated that a positive parent-child relationship could contribute to better well-being. Furthermore, higher perceived social support could also lead to higher well-being among Malaysian LGBTQ emerging adults. Besides that, having negative parent-child relationships could result in poorer well-being. Malaysian LGBTQ emerging adults who experience perceived discrimination could also have lower well-being. The integration of Minority Stress Theory and Relational Regulation Theory also supported the findings of this study. Overall, this paper expands the existing knowledge on the importance of positive and negative parent-child relationships, perceived social support, and perceived discrimination as predictors of well-being among Malaysian LGBTQ emerging adults. Interventions to improve the well-being of LGBTQ emerging adults should be organized, and policies to reduce discrimination against the LGBTQ community in Malaysia should be taken into account to increase their well-being